Peran Strategis Kepala Sekolah dalam Perencanaan dan Implementasi Projek Penguatan Profil Pelajar Pancasila: The Principal's Strategic Role in Planning and Implementing the Pancasila Student Profile Strengthening Project - Yani, Nurmaningsih; Febrina , Rifka; Hutabarat, Rinto; Asmendri, Asmendri; Sari, Milya (Thawalib: Jurnal Kependidikan Islam, 2024)
The values of Pancasila in the project include faith, diversity, mutual cooperation, independence, critical thinking, and creativity, with the school principal playing an essential role in guiding and managing the learning process. This study focuses on the principal's key role in planning and implementing the Pancasila Student Profile Strengthening Project at State Senior High School 1 Sawahlunto. The research employs a descriptive qualitative approach with a case study method. Data was collected through in-depth interviews, direct observation, and document analysis. Data processing involved condensation, presentation, and drawing conclusions. To ensure accuracy and reliability of the information, source triangulation was conducted. The findings indicate that the planning phase includes forming a facilitator team, identifying school readiness, organizing dimensions, themes, and time allocation for the Pancasila student profile strengthening project, creating project modules, and designing reporting strategies. In the implementation phase, each class follows the learning activities based on the assigned themes and projects, with the principal collaborating with the community, local organizations, and industries to support learning. This activity positively impacts the development of students' character, aligned with Pancasila values.